The “soltura de memes” in the prison of ex-president Michel Temer (MDB-SP): the use of humor and the themes highlighted - Marques, Rodolfo Silva; Conceição, Bruno da Silva (Brazilian Journal of Science, 2022)
In March 2019, former President of the Republic Michel Temer (2016-2018), of the MDB, was arrested, after an operation by the Federal Police, following a decision by federal judge Marcelo Bretas (TRF2-RJ). The operation included the arrest of several other politicians linked to Michel Temer, such as the former minister and governor of Rio de Janeiro, Moreira Franco, and Colonel João Baptista Lima Filho. In successive and articulated acts, Temer’s arrest generated a great repercussion in the media, especially on the internet. Such media reflex was noticed on news portals, looking for the causes and consequences of arrests, as well as in the construction of several memes, in general with a jocular connotation, dealing, pejoratively, with the arrest of the former president. In the present work, we seek to identify how memes were used in this political scandal, with consequences for other case analyses. An imagery assessment is applied, as a methodological path, to understand the rapid social mobilization in the use of memes, especially in political terms, in addition to the use of literature review. As conclusions, the use of humor memes is identified as a way of disqualifying the former president’s image with some pejorative references to Temer’s family environment, something very peculiar in this type of event.